Rufomycin Exhibits Dual Effects Against Mycobacterium abscessus Infection by Inducing Host Defense and Antimicrobial Activities - Park, Cho Rong; Paik, Seungwha; Kim, Young Jae; Kim, Jin Kyung; Jeon, Sang Min; Lee, Sang-Hee; Whang, Jake; Cheng, Jinhua; Suh, Joo-Won; Cao, Jin; Shetye, Gauri; Chen, Shao-Nong; et al. (Frontiers in Microbiology, 2021)
Nontuberculous mycobacterial (NTM) pulmonary infection is often aggravated due to antibiotic resistance issues. There is a need for development of new drugs inducing both host immune responses and antimicrobial activities. This study shows that the rufomycins 4/5/6/7 (Rufomycin 4-7), which targets ClpC1 as a subunit of caseinolytic protein complex ClpC1/ClpP1/ClpP2 of mycobacteria, exhibits a dual effect in host innate defense and in vivo antimicrobial activities against rough morphotype of Mycobacterium abscessus (Mabs-R), a clinically severe morphotype that causes hyperinflammation. Rufomycin 4-7 treatment showed antimicrobial effects against Mabs pulmonary infection in vivo and in macrophages. In addition, Rufomycin 4-7 significantly decreased inflammation, but enhanced the autophagy/lysosomal genes through upregulation of nuclear translocation of transcription factor EB (TFEB). Furthermore, Rufomycin 4-7 treatment effectively inhibited mitochondrial damage and oxidative stresses in macrophages during Mabs-R infection. Collectively, Rufomycin 4-7-mediated dual effects inducing both antimicrobial activities and host immune defense might confer an advantage to treatment against Mabs-R infection.